Randomized and double-blind comparison of clinical visual outcomes of 2 EDOF intraocular lenses. Issue 4 (April 2023) - Scheepers, Marius A.; Hall, Brad
Abstract : Symfony and Vivity EDOF IOLs provide similarly good visual outcomes. The Symfony group had increased reports of some visual disturbances, notably the frequency, severity, and bothersomeness of starbursts and glare. Abstract : Purpose: To assess and compare the visual disturbance profiles of 2 extended depth-of-focus (EDOF) intraocular lenses (IOLs). Setting: Private practice (West Kootenays, British Columbia, Canada). Design: Prospective, randomized, single-surgeon study. Methods: This was a double-blind prospective study of 138 eyes (69 patients) that underwent bilateral implantation of 1 of 2 EDOF IOLs. Participants were randomized to either the Symfony group or the Vivity group. Outcome measures included Questionnaire for Visual Disturbances; binocular corrected distance visual acuities at distance (6 m), intermediate (66 cm), and near (40 cm); and refractive outcomes. Results: At 3 months postoperatively, 21 patients (60%) reported not experiencing glare in the Symfony group compared with 30 (88%) in the Vivity group, a difference of 28% ( P = .008). Reports of experiencing starbursts were also significantly different between the Symfony and Vivity groups (23 participants [66%] Symfony and 30 participants [88%] Vivity; P = .027). In addition, 12 participants (34%) reported "moderate" or "severe" starbursts in the Symfony group compared with 3 (9%) in the Vivity group, a difference of 25% ( P = .019). Visual acuities and refractive outcomes were similar between groups. Conclusions: Both EDOF lenses provide good visual outcomes at distance and intermediate with acceptable near vision. The Symfony group had increased reports of some visual disturbances, notably the frequency, severity, and bothersomeness of starbursts and glare.